Multifactor equity modelling using random coefficents. - Lim, Andrew Tou Nan. (2008)
This dissertation aims to develop a model of equity risk and return for applications in portfolio and risk management. The methodology that is used in this dissertation is based on the concepts of random coefficients regression.